A method of perspective normalization for video images based on map data. Issue 1 (2nd January 2020) - Lin, Bingxian; Xu, Changlu; Lan, Xin; Zhou, Liangchen
ABSTRACT: Objective perspective distortion is a problem that needs to be solved by video surveillance analysis. Compared with the street scene method, which depends on prior knowledge of the scene or 3D scene of the dedicated hardware recovery scene, the commonly used perspective distortion correction method is based on the linear relationship to monitor a video image in perspective normalization. However, the distortion caused by perspective imaging is nonlinear, and the linear perspective normalization model cannot guarantee the accuracy of the correction in the scene where the perspective phenomenon is evident. An image normalization method based on map data is proposed to solve this problem. A nonlinear perspective correction model is introduced by establishing a single relation between video image space and map space. With selected control points between image and map, we can calculate homography matrix in order to build the perspective correction model, which is computed to know the single pixel real size in map. The proposed perspective correction model is applied to the moving target detection. The results of the linear correction model and the proposed nonlinear correction model prove the validity and practicability of the method.